Vendor testimonials on Vendor Business School curriculum - Gimutao, Kaymart; Bertuso, Arma; Ricarte, Phoebe; Labitag, Ralfh Ronnel; Caoile, Ginia Pauline; Prain, Gordon; Heck, Simon; Alonso, Silvia (CGIAR System Organization, 2024)
The Vendor Business School (VBS) is an innovative program of CGIAR Resilient Cites Initiative implemented in Quezon City and Nairobi for piloting. VBS aims to empower small food vendors by providing them with vital knowledge, skills, and resources to overcome the challenges of their daily business operations and improve their food safety measures. The video showcases the testimonials of several stall vendors from private and public markets and hawkers after graduating from the VBS on their learnings in the vendor business school curriculum. This was shared during the Urban Food System Policy Forum organized by the CGIAR Resilient Cities Initiatives and Quezon City Government held last November 6, 2024. Overall, the testimonials show the positive impact of the VBS curriculum and their learning on their business and personal growth.